Neurocritical care physicians’ doubt about whether to withdraw life-sustaining treatment the first days after devastating brain injury: an interview study - Annette Robertsen; Eirik Helseth; Jon Henrik Laake; Reidun Førde (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2019)
Abstract Background Multilevel uncertainty exists in the treatment of devastating brain injury and variation in end-of-life decision-making is a concern. Cognitive and emotional doubt linked to making challenging decisions have not received much attention. The aim of this study was to explore physicians´ doubt related to decisions to withhold or withdraw life-sustaining treatment within the first 72 h after devastating brain injury and to identify the strategies used to address doubt. Method Semi-structured interviews were conducted with 18 neurocritical care physicians in a Norwegian trauma centre (neurosurgeons, intensivists and rehabilitation specialists) followed by a qualitative thematic analysis. Result All physicians described feelings of doubt. The degree of doubt and how they dealt with it varied. Institutional culture, ethics climate and individual physicians´ values, experiences and emotions seemed to impact judgements and decisions. Common strategies applied by physicians across specialities when dealing with uncertainty and doubt were: 1. Provision of treatment trials 2. Using time as a coping strategy 3. Collegial counselling and interdisciplinary consensus seeking 4. Framing decisions as purely medical. Conclusion Decisions regarding life-sustaining treatment after devastating brain injury are crafted in a stepwise manner. Feelings of doubt are frequent and seem to be linked to the recognition of fallibility. Doubt can be seen as positive and can foster open-mindedness towards the view of others, which is one of the prerequisites for a good ethical climate. Doubt in this context tends to be mitigated by open interdisciplinary discussions acknowledging doubt as rational and a normal feature of complex decision-making.